Obesity in pregnancy - Bernardo, Diana Filipa Salvador; Carvalho, Carlos Manuel Baptista; Mota, Jorge; Santos, Paula Clara (Seven Editora, 2024)
The 2020 edition of the Institute of Health Statistics in Portugal provides information on the health of pregnant women, childbirth and newborns. In 2022, there were 829,807 births in Portugal, 36% of which involved instrumental delivery by cesarean section. Regarding simple deliveries, 93.2% of the parturients had a pregnancy lasting between 37 and 41 weeks (PORDATA, 2023) and the mean age of pregnant women was 32.2 years. The birth rate in Portugal has been decreasing and maternal age has been increasing, with 97.4% of pregnancies occurring between the ages of 30 and 34 (PORDATA, 2023). DOI:https://doi.org/10.56238/sevened2023.007-069